2022
DOI: 10.1039/d2ja00140c
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid method combining discharge-assisted laser induced breakdown spectroscopy with wavelet transform for trace elemental analysis in liquid targets

Abstract: Laser-induced breakdown spectroscopy (LIBS) represents a highly promising detection technology in quantitative determination of trace elements in liquid. However, due to the plasma fast quenching, liquid level instability, and limited...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Therefore, the LOD for Ca is ultimately decreased from 1.9 mg/L in SP-LIBS-SWS to 86 μg/L in DA-LIBS-FPS, thereby resulting in a 22-fold improvement in quantitative analytical performance. It was reported that the LODs of Ba and Ca in the liquid targets were located at the level of several ppm for SP-LIBS and at subppm for other enhanced LIBS techniques. ,,, In contrast, compared with the reported detection levels, the LOD in DA-LIBS-FPS is reduced by 1–2 orders of magnitude, as shown in Table .…”
Section: Results and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Therefore, the LOD for Ca is ultimately decreased from 1.9 mg/L in SP-LIBS-SWS to 86 μg/L in DA-LIBS-FPS, thereby resulting in a 22-fold improvement in quantitative analytical performance. It was reported that the LODs of Ba and Ca in the liquid targets were located at the level of several ppm for SP-LIBS and at subppm for other enhanced LIBS techniques. ,,, In contrast, compared with the reported detection levels, the LOD in DA-LIBS-FPS is reduced by 1–2 orders of magnitude, as shown in Table .…”
Section: Results and Discussionmentioning
confidence: 88%
“…It was reported that the LODs of Ba and Ca in the liquid targets were located at the level of several ppm for SP-LIBS and at subppm for other enhanced LIBS techniques. 7,14,21,22 In contrast, compared with the reported detection levels, the LOD in DA-LIBS-FPS is reduced by 1−2 orders of magnitude, as shown in Table 1.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors developed the device as a miniaturised, low-cost and low-power consumption instrument. Xu et al 140 developed a hybrid method that combined discharge-assisted LIBS with wavelet transform de-noising, for trace elemental analysis in liquid samples ( e.g. , oil pollutants).…”
Section: Laser-based Atomic Spectrometrymentioning
confidence: 99%
“…The last paper in this section was by Xu et al and described a hybrid method combining discharge assisted LIBS with wavelet transform for trace elemental analysis in liquid targets . 95 Although LIBS is a highly promising detection technology for the quantitative determination of trace elements in liquids, there are several challenges to overcome. This is because of the fast plasma quenching, liquid level instability and limited laser-energy absorption making rapid real-time quantitative detection of trace elements with high-sensitivity in liquid targets very difficult.…”
Section: Organic Chemicals and Materialsmentioning
confidence: 99%